Geological controls on the present temperature field of the western Sverdrup Basin, Canadian Arctic Archipelago. (20th January 2017) - Chen, Zhuoheng; Grasby, Stephen E.; Dewing, Keith; Osadetz, Kirk G.; Brent, Tom
Abstract: Analysis of current temperature data in the Canadian Arctic Archipelago results in the recognition of two major thermal regimes. High temperature regions are observed where salt diapirs and salt cored anticlines are present. Low temperature fields are observed along the western and southern basin margins and around Cornwall‐Amund Ringnes islands, where regional Mesozoic aquifers are exposed to surface, connected to basin boundary faults, or regional unconformities. Meteoric and Holocene sub‐glacial water recharge are inferred to be responsible for the low geothermal regime and low formation water salinity. Neither exhumation associated with the Eocene "Eurekan" orogeny nor volcanic intrusion associated with opening of Amerasia Basin in late Jurassic‐early Cretaceous have been interpreted to be a significant influence on the present day temperature field, although thermal indicators show evidence of elevated thermal alteration of organic matter pointing to earlier, but now dissipated, thermal anomalies.